Pemanfaatan Pepaya Muda Untuk Meningkatkan Pendapatan Ibu Rumah Tangga RT 02 RW 20 Pandau Jaya Kabupaten Kampar - Ika Wulandari; Dora Amelya; Desfita Eka Putri (LPPM POLITEKNIK LP3I, 2023)
The LP3I Pekanbaru Polytechnic community service team carries out routine activities every semester, which this time are held in Pandau Jaya Village, Jalan Kapling RT 02, RW 20, Kampar Regency. This activity takes the form of training for housewives in making papaya chips, where papaya fruit is very easy to find anywhere, the price is affordable and on average, several houses use their yards by planting papaya fruit. The aim of the training that we provide from the community service team at LP3I Pekanbaru Polytechnic is so that housewives can utilize their time by utilizing plants in their yard, apart from being a healthy family snack, they can also earn side income, which aims to help the family economy and The next target is the formation of papaya stick MSMEs in Pandau Jaya Village.